A Philosophical Study of Stoicism in the Perspective of the Qur’an: A Thematic Analysis of the Concepts of Patience (Sabr), Contentment (Ridha), and Trust in God (Tawakkul) - Safitri, Lutfi Dewi (Nizham Jurnal Studi Keislaman, 2025)
This study aims to examine the meaning of the concepts of patience (sabr), contentment (ridha), and trust in God (tawakkul) in the Qur’an, as well as to explore their intersections and distinctions with Stoic principles. The background of this study arises from the phenomenon of contemporary Muslim spirituality, which often interprets these three concepts in a narrow sense, whereas in classical Islamic tradition they represent an active form of spirituality imbued with reflection and self-control. This research employs a qualitative approach with the thematic exegesis method (maudhu’i), combined with the ethical framework of Stoicism as an interpretative analytical tool. Thematic data analysis revealed five main themes: (1) patience as active perseverance in facing trials, (2) contentment as sincere acceptance of destiny with faith in God’s wisdom, (3) trust in God as submission of outcomes after maximal effort, (4) the synergistic relationship of the three concepts in shaping holistic spirituality, and (5) their impact on character maturity and psychological resilience. The findings indicate convergence with Stoic principles apatheia, amor fati, and prohairesis yet remain distinct in their theological dimension emphasizing submission to God.